3D Co-culture of Cancer-Associated Fibroblast with Oral Cancer Organoids. (February 2021) - Zhao, H.; Jiang, E.; Shang, Z.
Limits of the available model have, in the long term, challenged the studies of cancer-associated fibroblasts (CAFs) and their interplay with cancer stem cells, one of the key driving forces of patients with oral squamous cell carcinoma (OSCC). In the present study, the 3-dimensional organoid model was employed to investigate whether co-culture with paralleled CAFs promotes stem-like properties of OSCC. Experimentally, tumor organoids and paralleled CAFs were generated from patients with OSCC. Then, the CD44 + cells in organoids were sorted out by flow cytometry and co-cultured with CAFs in Matrigel. The results showed that co-culture with CAFs enhances the organoid-forming ability of CD44 + cells and that this effect was blocked when production or uptake of lactate in CAFs or CD44 + cells was inhibited. Furthermore, the expression levels of CD44 and OCT-4 were detected in organoids incubated with lactate, via immunofluorescence or Western blot assay. The results demonstrated that treatments with lactate promote the organoid-forming ability of CD44 + cells, as well as the expression of CD44 and OCT-4 at the protein level in OSCC organoids.